Pemberdayaan Kelompok Wanita Tani (KWT) Melalui Pembagian Benih Sayuran Dalam Rangka Mendukung Ketahanan Pangan Keluarga - Umi Nur Solikah; Mohamad Ihsan; Arifah Husna; Rehino Yanu Seto; Chanda Firdaus; Mufida Diah Lestari (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2023)
Vegetables play an important role in human life. Because vegetables are a source of vitamins and minerals that are good for health. The large number of cases of stunting in children today is caused by, among other things, a lack of nutritious food, including vegetables. In general, the people of Colomadu District, Karanganyar Regency do not fully utilize their home gardens. By distributing vegetable seeds to women farmer groups (KWT) in Colomadu District, the Women Farmer Groups can optimize their yard land so as to support the Framework for Supporting Family Food Security. Steps taken in the community service activity "Empowerment of Women Farming Groups (KWT) through the distribution of vegetable seeds in order to support family food security. including: First step, Coordination with the head of the Neighborhood Association (RT), this activity is the first step in community service activities, the purpose of this activity is to ask for permission to carry out community service activities and ask about what the Women's Farmers Group (KWT) needs. in order to support family food security. The second step, namely implementation, this activity is a series of the first step, after a meeting point has been reached for coordination activities, the day for carrying out community service activities is determined.